2012
DOI: 10.1128/aac.06478-11
|View full text |Cite
|
Sign up to set email alerts
|

Different Biosynthetic Pathways to Fosfomycin in Pseudomonas syringae and Streptomyces Species

Abstract: cFosfomycin is a wide-spectrum antibiotic that is used clinically to treat acute cystitis in the United States. The compound is produced by several strains of streptomycetes and pseudomonads. We sequenced the biosynthetic gene cluster responsible for fosfomycin production in Pseudomonas syringae PB-5123. Surprisingly, the biosynthetic pathway in this organism is very different from that in Streptomyces fradiae and Streptomyces wedmorensis. The pathways share the first and last steps, involving conversion of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 59 publications
0
74
0
Order By: Relevance
“…E. coli strains were grown in LB broth at 37°C with standard antibiotic concentrations. WM4489, a DH10B derivative engineered to control copy-number of oriV-based plasmids (40), was used as the host strain for all plasmids generated in this study (Table S2). Plasmid copy number was increased by adding sterile rhamnose to a final concentration of 10 mM.…”
Section: Methodsmentioning
confidence: 99%
“…E. coli strains were grown in LB broth at 37°C with standard antibiotic concentrations. WM4489, a DH10B derivative engineered to control copy-number of oriV-based plasmids (40), was used as the host strain for all plasmids generated in this study (Table S2). Plasmid copy number was increased by adding sterile rhamnose to a final concentration of 10 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Presumably, these enzymes act to provide autoresistance to the producers. Another such kinase, originally called FosC and found in the fosfomycin producer P. syringae, is actually an ortholog of FomA (Kim et al 2012). …”
Section: Fosfomycin-modifying Enzymesmentioning
confidence: 99%
“…Because this initial reaction is thermodynamically unfavorable, net synthesis of phosphonates requires a thermodynamically favorable step immediately following PepM. Initial studies identified phosphonopyruvate decarboxylase (Ppd) as the enzyme providing this driving force; however, recent data show that other driving reactions exist (31,32). Subsequent biosynthetic steps diverge to create a wide range of C-P biomolecules.…”
mentioning
confidence: 99%